Pituitary-Thyroid System in Rats of Different Ages Under Short-Term Cold Exposures - Lomako, Viktoria; Shylo, Oleksandr; Samokhina, Lubov (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(2):143–149